Visualization to compare karate motion captures - Urribarri, Dana K. (2019)
Multi-dimensional time series from motion capture (MoCap) provide a rich source of data for human motion analysis, yet they are difficult to process and compare. We address MoCap data related to Karate katas, containing predefined sequences of movements, executed independently by several subjects with different timing and speed. We propose a combination of signal processing and data visualization techniques to analyze the misalignment between data from different subjects. We present a web app that implements this proposal, providing a visual comparison of time series, based on Dynamic Time Warping.